The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1970
DOI: 10.1111/j.1744-6570.1970.tb01368.x
|View full text |Cite
|
Sign up to set email alerts
|

INDIVIDUAL DIFFERENCES AND ORGANIZATIONAL CLIMATE II: MEASUREMENT OF ORGANIZATIONAL CLIMATE BY THE MULTI‐TRAIT, MULTI‐RATER MATRIX1

Abstract: THIS paper has two major purposes: (1) to present more detailed information than has been previously reported (Schneider & Bartlett, 1968) on the initial development of a measure of organizational climate; and (2) to explore a number of issues surrounding the question: who's view of an organization's climate do you use?The Model and The MeasureThe Model I n a previous article (Schneider and Bartlett, 1968) a personnel selection and classification model was presented indicating that the traditional bi-variate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
8

Year Published

1979
1979
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 16 publications
0
41
0
8
Order By: Relevance
“…Finally, the organizational system limits the degree of freedom in the control of decision-making processes, and, additionally, the individual, being influenced by a decision, can be a further restriction to the decision-making process. Previous research (e.g., Schein, 1991;Schneider and Bartlett, 1970;Zey-Ferrell et al, 1979) confirmed the reliability of such assumptions and, all in all, for this study managerial personnel are assumed to give a good indication of perceptions of the ethical climates. It is, however, recognized that studies at more hierarchical levels would improve the validity and reliability of the results.…”
Section: The Ethical Climate Of Danish Firms 669mentioning
confidence: 89%
“…Finally, the organizational system limits the degree of freedom in the control of decision-making processes, and, additionally, the individual, being influenced by a decision, can be a further restriction to the decision-making process. Previous research (e.g., Schein, 1991;Schneider and Bartlett, 1970;Zey-Ferrell et al, 1979) confirmed the reliability of such assumptions and, all in all, for this study managerial personnel are assumed to give a good indication of perceptions of the ethical climates. It is, however, recognized that studies at more hierarchical levels would improve the validity and reliability of the results.…”
Section: The Ethical Climate Of Danish Firms 669mentioning
confidence: 89%
“…Poucos ainda são os estudos etnográficos ou pesquisas experimentais conduzidos para a avaliação do construto (Ouchi & Wilkins, 1985). Sendo assim, diferentes escalas foram desenvolvidas para a mensuração do construto em âmbito internacional (Friedlander & Margulies, 1969;Hellriegel & Slocum, 1974;House & Rizzo, 1972;Litwin & Stringer, 1968;Payne & Pheysey, 1971;Pritchard & Karasick, 1973;Schneider & Bartlett, 1970;Toro, 2001) e nacional (Coda, 1997;Martins et al, 2004;Laros & Puente-Palacios, 2004;Rizatti, 2002;Souza, 1977Souza, , 1980Souza, , 1982Souza, , 1983Tamayo, 1999).…”
Section: Considerações Finaisunclassified
“…Klimato tyrinėtojai (Sims, Lafollette 1975;Muchinsky 1976;Ireland et al 1978;Landy 1985;Koys, DeCotiis 1991;Simons, Naylor-Stables 1997;Furhnam 1999;Fey, Beamish 2001;Mok, Au-Yeung 2002) išskyrė šiuos svarbiausius organizacijos klimato veiksnius: savarankiškumo charakteristika įvertina darbo vietoje jaučiamą spaudimą ir tai, kaip organizacijos vadovybė akcentuoja aukštus darbo atlikimo standartus; struktūros charakteristika nustato, kaip individas suvokia vadovybę; atlygio charakteristika nustato, kiek darbuotojams yra aiš-ki paaukštinimo politika, bendroji organizacijos politika, struktūra ir darbo funkcijos; rizikos charakteristika nustato organizacijos vadovų priimamų sprendimų rizikos laipsnį; nuoširdumo charakteristika nusako komunikaciją tarp vadovų ir darbuotojų, norą priimti ir įgyvendinti pavaldinių idėjas; paramos charakteristika apibūdina, kaip vadovai konsultuoja, moko darbuotojus; toleravimo ir konfliktų charakteristika apibrėžia, kaip asmuo suvokia bendradarbius ir kitus organizacijos žmones; darbo standartų charakteristika nurodo, ar organizacijos vadovai supažindina darbuotojus su jų tiesioginiu darbu, ar jiems aiškios užduotys. Campbell et al (1970) nagrinėjo jau atliktus organizacijos klimato tyrimus remdamiesi Kahn et al (1964), Litwin ir Stringer (1968), Taguiri (1968) ir Schneider, Bartlett (1970) darbais ir rado šiuose tyrimuose keturis bendrus aspektus: savarankiškumą, struktūrą, atlygį, paramą (šilumą ir palaikymą) (Campbell et al 1970;Meglino 1976;Ibbetson, Newell, 1988;Furnham 1999;Litwin, Stringer 1968;Taguiri 1968;Schneider, Bartlett 1970).…”
Section: Organizacijos Klimatas: Raida Ir Sandaraunclassified